2022
DOI: 10.3390/antibiotics11111600
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Mixed Impact on Hospital Antimicrobial Stewardship Activities: A Qualitative Study in UK-Based Hospitals

Abstract: Antimicrobial resistance (AMR) is a well-known global threat due to the subsequent increase in antimicrobial usage. Several antimicrobial stewardship (AMS) strategies have been implemented to curb irrational prescribing and reduce the AMR burden. However, since the beginning of the COVID-19 pandemic, it has enormously impacted the healthcare system and jeopardized public health, causing millions of deaths globally. Our semi-structured qualitative study aimed to explore the impact of COVID-19 on AMS activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 50 publications
3
9
0
Order By: Relevance
“…Several factors affected AMS during the pandemic, including staff vacancies, redeployment of AMS staff to other duties and meeting the burden related to COVID-19 and lack of resources. 49 Reducing the use of Watch antibiotics and increasing the use of Access antibiotics where availability is low is emphasized as an overall goal. As a target by 2023, 60% of all antibiotics consumed must come from the group of antibiotics at lowest risk of resistance, that is, the Access group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors affected AMS during the pandemic, including staff vacancies, redeployment of AMS staff to other duties and meeting the burden related to COVID-19 and lack of resources. 49 Reducing the use of Watch antibiotics and increasing the use of Access antibiotics where availability is low is emphasized as an overall goal. As a target by 2023, 60% of all antibiotics consumed must come from the group of antibiotics at lowest risk of resistance, that is, the Access group.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of hospital data showed a decrease in the use of the Access group and an increase in the use of the Watch group. Several factors affected AMS during the pandemic, including staff vacancies, redeployment of AMS staff to other duties and meeting the burden related to COVID‐19 and lack of resources 49 . Reducing the use of Watch antibiotics and increasing the use of Access antibiotics where availability is low is emphasized as an overall goal.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study conducted in the United Kingdom indicated that ASP ward rounds had been implemented effectively before the pandemic, while during the pandemic, they were neglected due to staff pressure (Khan et al, 2022 ). Another study found that engagement of the ASP teams during the COVID-19 pandemic was affected by the pandemic or almost not functioning (Borek et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In response to this crisis, antimicrobial stewardship (AMS) initiatives have become crucial, promoting the responsible use of antibiotics to mitigate the risks associated with AMR [ 7 , 8 ]. The importance of AMS programs is highlighted by the rapid spread of AMR, which complicates the management of infectious diseases [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%